A systematic review of tetracycline resistance genes in animals and derived products in Latin America and the Caribbean - Vásquez-Jaramillo, Laura; Cardozo-Herrera, Laura Katerine; Correa Valencia, Nathalia María Del Pilar (Brazilian Journal of Veterinary Research and Animal Science, 2023)
We aimed to systematize and assess scientific information on tetracycline (TET) resistance genes in animals, products, and by-products in the Latin America and the Caribbean (LAC) region. PRISMA guidelines were followed. Only original articles published in peer-reviewed journals were considered. Sixty articles published between 2003 and 2023 met the inclusion criteria. The geographical areas of study were Brazil, Mexico, Chile, and Costa Rica, and, to a lesser extent, Colombia, Bolivia, Cuba, Jamaica, Puerto Rico, and Uruguay. The studies were related to livestock, wild animals, and pets. The most common isolated bacteria were Escherichia coli and Salmonella spp. The tet genes found in higher frequency in the samples or isolates evaluated were tetA, tetB, tetM, tetL, tetK, tetC, tetO, tetD, tetG, tetW, tetS, tetQ, tetE, tetH, tetJ, tetZ, and tetY. Studies evaluating the presence of tet genes in animals in LAC are limited despite TET being antibiotics widely used in animals. It is necessary to establish cross border public policies that allow the constant training of medical and related personnel regarding the responsible use of antibiotics in animals and the effective monitoring of the phenomenon in the region.